Nursing care in threatened preterm labor in the Obstetrics and Gynecology Department of a hospital - Bueno-Huaman, Ruth N; Villanueva-Sanchez, Carmen; Vivanco-Hilario, Sofía D.; Morales-García, Wilter C. (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
The threat of preterm labor, a pathology endangering the lives of both mother and baby, affects one in ten births and is a serious public health issue. This research aimed to manage the nursing care process for a 35-year-old pregnant woman with a threat of preterm labor, using a purely qualitative approach in a single case study, applying the five stages of the nursing care process. In the assessment stage, Maryori Gordon’s 11 functional patterns guide was used, identifying 10 nursing diagnoses based on NANDA-I Taxonomy II, prioritizing: labor pain, risk of maternal/fetal dyad alteration, and infection control. The care plan was developed using NOC and NIC classifications. During the implementation stage, nursing care focused on pain management, prenatal fetal status, and infection control. These were evaluated by comparing baseline scores with achievement scores, resulting in an updated care plan with changes scored at +1, 0, and +2. In conclusion, the nursing care process was managed, providing quality and humanized care to the patient